Productivity of representative breeds of important cattle groups in Africa - Trail, J.C.M. (1985)
Describes the productive performance of main cattle groups in Africa in relation to the ecological zones of the region. Contributions of past research work in breed evaluation and breed characterization studies that highlight the value of such work for each of the three major indigenous cattle groups of Africa: Africander, Tswana and Tuli cattle of the Sanga group; Boran and Small East African Zebu cattle of the humped zebu group; and N'Dama and West African Shorthorn cattle of the indigenous taurine group included.